2005
DOI: 10.1016/j.febslet.2005.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin cofactor A gene silencing in mammalian cells induces changes in microtubule cytoskeleton, cell cycle arrest and cell death

Abstract: Microtubules are polymers of a/b-tubulin participating in essential cell functions. A multistep process involving distinct molecular chaperones and cofactors produces new tubulin heterodimers competent to polymerise. In vitro cofactor A (TBCA) interacts with b-tubulin in a quasi-native state behaving as a molecular chaperone. We have used siRNA to silence TBCA expression in HeLa and MCF-7 mammalian cell lines. TBCA is essential for cell viability and its knockdown produces a decrease in the amount of soluble t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 36 publications
5
41
0
Order By: Relevance
“…The Mecp2 gene was not on the list because a truncated mRNA corresponding to the 3′ coding region of Mecp2, where Affymetrix probe sets hybridize, was expressed in KO neurons. Among the identified differentially expressed genes, Prefoldin 5 is involved in actin and tubulin folding and cytoskeleton formation (Hartl and Hayer-Hartl, 2002;Nolasco et al, 2005), and Syndecan 2 has been shown to be critical for synaptogenesis (Ethell and Yamaguchi, 1999;Ethell et al, 2001). We have confirmed that the expression levels of both Syndecan 2 and Prefoldin 5 mRNA were higher in KO neurons using Real time PCR analyses (Fig 5D-E).…”
Section: Altered Gene Expression Of Synaptic Proteins In Mecp2-deficisupporting
confidence: 66%
“…The Mecp2 gene was not on the list because a truncated mRNA corresponding to the 3′ coding region of Mecp2, where Affymetrix probe sets hybridize, was expressed in KO neurons. Among the identified differentially expressed genes, Prefoldin 5 is involved in actin and tubulin folding and cytoskeleton formation (Hartl and Hayer-Hartl, 2002;Nolasco et al, 2005), and Syndecan 2 has been shown to be critical for synaptogenesis (Ethell and Yamaguchi, 1999;Ethell et al, 2001). We have confirmed that the expression levels of both Syndecan 2 and Prefoldin 5 mRNA were higher in KO neurons using Real time PCR analyses (Fig 5D-E).…”
Section: Altered Gene Expression Of Synaptic Proteins In Mecp2-deficisupporting
confidence: 66%
“…S. pombe cofactor A is dispensable for cell viability (13) and is also not required for tubulin folding using an in vitro tubulin folding assay (1). In contrast, Nolasco et al (46) found that loss of cofactor A in mammalian cells led to a decrease in soluble tubulin, microtubule alterations, and a loss of cell viability.…”
Section: Discussionmentioning
confidence: 87%
“…It has been found, for example, that cofactor A has a highly extended helical conformation (33), and we speculate that it could potentially interact with H11 and H12, protecting the quasi-native protein from the degradation pathway. Evidence to support this idea has recently come from the observation that depletion of cofactor A using siRNA causes a large reduction in cellular tubulin (34). The inability of either cofactor A or cofactor D to bind properly to the ␤-tubulin released from CCT might, thus, trigger its degradation.…”
Section: Discussionmentioning
confidence: 99%